Challenges of congenital heart disease in grown-up patients (Swiss Medical Weekly, 2017)
Nowadays, more than 90% of all children born with congenital heart disease (CHD) reach adult life. Although initially considered to be cured, the majority of them continue to need specialised follow-up because they require re-do interventions or are at increased risk of cardiovascular complications and premature death. Arrhythmias are the most common cause of unscheduled hospital visits for grown-up CHD (GUCH) patients, accounting for one third of emergency admissions in these patients. Some GUCH patients are also at increased risk for sudden cardiac death. The principles of arrhythmia management and the prevention of sudden cardiac death in GUCH patients are similar to those used in adults with acquired heart disease, but are not evidence based. Decompensated heart failure is the other leading cause of death. Conventional medical heart-failure therapy for left ventricular dysfunction is not effective in GUCH patients at highest risk of heart failure, i.e., those with right or single ventricular failure. Careful haemodynamic assessment and structural interventions are the first step to consider in GUCH patients presenting with heart failure symptoms. Adults with moderate or complex CHD and regular follow-up in specialised GUCH centres have a survival benefit compared with patients without such follow-up. Cardiac surgery in GUCH patients should be performed by surgeons trained in treatment of CHD, i.e., surgeons also operating on paediatric patients. A structured transition programme with a defined transfer of care from the paediatric to the adult care environment is important to avoid lapses of care in today’s adolescents with CHD. For GUCH patients with an intervention performed decades ago and no specific cardiac follow-up in later life, referral to a specialised GUCH centre is recommended and may save lives.